Triptolide exposure induces oxidative stress and decreases oocyte quality in mouse. (1st January 2023) - Hao, Qian-Qian; Xu, Zhi-Ran; Nie, Han; Qiao, Feng-Xin; Sun, Ming-Xin; Liu, Yue-Cen; Wang, Hai-Long; Qi, Zhong-Quan; Xu, Chang-Long; Liu, Yu
Abstract: Triptolide is a major active ingredient isolated from the traditional Chinese medicine Tripterygium wilfordii, which has anti-inflammatory, anti-cancer, and immunomodulatory effects. However, in clinical studies, triptolide has toxic side effects on the heart, kidney, liver and reproductive organs. With respect to female reproductive toxicity, damaging effects of triptolide on the ovary have been reported, but it has remained unknown whether oocytes are affected by triptolide. Therefore, this study established a concentration gradient of triptolide exposure in mice using 0 (control), 30, 60, and 90 μg triptolide/kg body weight/day administered by gavage. Triptolide administration for 28 d reduced body weight and ovarian weight and affected the developmental potential of oocytes. The triptolide-treated group exhibited meiotic failure of oocytes due to impaired spindle assembly, chromosome alignment, and tubulin stability. Triptolide was also found to induce mitochondrial dysfunction, autophagy and early apoptosis, iron homeostasis, and abnormal histone modifications. These adverse effects could be associated with oxidative stress induced by triptolide. In conclusion, our findings suggest detrimental effects of triptolide on mouse oocytes and, thus, on female reproduction. Graphical abstract: Image 1 Highlights: Triptolide exposure reduces mouse oocyte development ability. Triptolide exposure disrupts spindle organization in mouse oocytes. Triptolide exposure induces oxidative stress in mouse oocytes.